Candida Albicans Osteomyelitis after Chest Wall Blunt Trauma: A Case Report - Minervini, Fabrizio (Case Rep Surg, 2021)
Fungal osteomyelitis is a rare disease that can occur in immunocompromised patients. We report a case of a patient with a primary rib osteomyelitis after a blunt trauma of the chest wall. Aggressive surgical debridement along with antifungal therapy was the cornerstone of the disease management in this patient.